INTERNATIONAL STANDARDS OF FINANCIAL SUPPORT TO THE POPULATION IN NEED OF SOCIAL PROTECTION - Sholdarov Dilshod Azimiddin o‘g‘li (Journals Park Publishing, 2025)
The article presents an analysis of international standards of financial support for people in need of social protection, focusing on the main principles of the social protection system around the world, international standards, best practices, problems and opportunities for improvement. Drawing on human rights principles, including the right to social security and the right to an adequate standard of living, the study examines the diversity of approaches to financial support across countries, targeting, and eligibility criteria and makes recommendations for strengthening mechanisms for financial support for vulnerable populations.
Keywords: Financial Support; Human Rights; International Standards; International Covenant on Economic, Social and Cultural Rights; Social Protection; Social Protection Systems; Sustainable Development Goals; Vulnerable Populations.